Using Lean Six Sigma to Improve First-Case Delays in Pediatric Endoscopy. (November 2021) - Cardini, Jeff
Abstract : Pediatric endoscopy is an essential clinical practice used to diagnose and treat gastrointestinal diseases in children. Moreover, pediatric endoscopy programs require a clinically and technically specialized unit organized around performing endoscopic procedures with high levels of training and skill. With the volume of endoscopic procedures steadily rising in large academic medical centers each year, achieving operational efficiency has become critical to running a successful endoscopy program.